Wireless infra-red computer control - He, Xiaofei. (2008)
The purpose of this project is to find out whether there are other means to improve infra-red (IR) communication range. In this project, IR wireless mouse was developed, IR mouse is not a new device, actually there are many kinds of IR mice in the market, but those available mice often have a control distance less than 2 meters.